(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
A Blurb refers to a summary or promotional piece accompanying a creative work. It is usually deployed to function as a marketing or persuasive strategy aimed at getting the potential customers to buy and read a book. This study examined the blurbs of motivational books through pragma-stylistic approach. It investigated various pragma-stylistic devices deployed in the selected blurbs in relation to the contexts in which they are used. Blurbs of motivational books written by Nigerian authors constituted the data for the study; the blurbs were selected because the books discuss various topical issues that are of interest to Nigerians. Furthermore, motivational books were considered appropriate for this study, because virtually everybody wants to be motivated in every area of life. The data for this study were drawn from purposively selected blurbs of ten (10) motivational books written by Nigerian authors. The data were analysed with insights drawn from Halliday’s Systemic Functional Linguistics. The study showed that the pragmatic features – reference, deixis, inference and allusion – play a prominent role in the composition of blurbs of motivational books written by Nigerian authorPragmatic features are employed in blurbs by Nigerian authors of motivational books as persuasive tools to convince readers to gladly buy the books. The study notes that the blurbs of motivational books by Nigerian authors are replete with reference, deixis, inference and allusion that play a great role in their structures.